Increasing the diversity of marigold (Tagetes sp.) by acute and chronic chemical induced mutation of EMS (Ethyl Methane Sulfonate) - DEWI YANNY LENAWATY; DEWI SUKMA; MUHAMAD SYUKUR; DEWA NGURAH SUPRAPTA; WARAS NURCHOLIS; SYARIFAH IIS AISYAH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lenawaty DY, Sukma D, Syukur M, Suprapta DN, Nurcholis W, Aisyah SI. 2022. Increasing the diversity of marigold (Tagetes sp.) by acute and chronic chemical induced mutation of EMS (Ethyl Methane Sulfonate). Biodiversitas 23: 1399-1407. Increasing the diversity of marigold (Tagetes sp.) can be carried out through chemical induction mutations with Ethyl Methane Sulfonate (EMS).This study aims to obtain the LC50value, determine the sensitivity level of plants, and obtain plant diversity of Tagetes sp.with EMS both acutely and chronically. The genetic material used in this study was derived from T. erecta genotype MG04 and T. patula genotype MG21. The acute mutation technique was performed by soaking the seeds in EMS concentration for 4 hours under 10 different concentration levels (0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.5%, 2.0%, and 3.0%). The chronic mutation technique was carried out by diluting the concentration of EMS LC501/10x, 1/100x, 1/1000x and immersion time of 6 hours, 24 hours and 48 hours. The study used a Completely Randomized Block Design. Observationswere made on the percentage of surviving plants, quantitative and qualitative characters. The data obtained were analyzed using Boxplot and ANOVA. The results showed that the LC50 value of T. erecta is 0.82% and LC50of T. patula is 1.87%, which means that the sensitivity level of T. erecta to EMS treatment is quite higher than T. patula. The acute application method shows a relatively low mutation rate and limited diversity of flower types. The chronic application method produced various flower shapes and whiter flower color in T. erectaand T. patula resulting in a redder flower color than the acute application method.